Penerapan Model Design Thingking dalam Perancangan Aplikasi Pengolahan Data LAKI Berbasis Website - Fuad Azhari; Nia Oktaviani (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This research involves designing a prototype application to simplify the processing of LAKI (Consultation and Information Services) data at the South Sumatra Provincial Archives Service. Based on the entire internship and system design process, it can be concluded that LAKI (Consultation and Information Services) data management in the Supervision Division of the South Sumatra Provincial Archives Service still requires improvements in terms of information systems and data governance. The previous manual recording process, using physical forms and spreadsheets, resulted in a high risk of data duplication, input errors, delays in information updates, and difficulties in data tracking and report preparation. This situation indicates that the manual system is no longer efficient due to the increasing volume of data and the need for faster and more integrated documentation. With this design, it is hoped that the archival data management process will be faster, more accurate, more secure, and in accordance with the principles of good governance. Therefore, the results of this design can make a tangible contribution to improving the quality of public services, particularly in the archival sector, and support efforts to modernize the digital-based supervision system within the South Sumatra Provincial Archives Service.